Mathematical Modeling and Sensitivity Analysis of the Existence of Male Calico Cats Population Based on Cross Breeding of All Coat Colour Types - Dani Suandi; Ira Prapti Ningrum; Amalia Nur Alifah; Nurul Izzah; Mazi Prima Reza; Imroatul Khoiriyah Muwahidah (Indonesian Bio-Mathematical Society, 2019)
The coat color of cats is normally governed by genes found on the X chromosome in both male chromosome XY and female chromosome XX. The meiosis failure in the process of gametogenesis leads to the birth of three-colored male cats caused by an excess of the X chromosome in the male chromosome type XY. The chromosome structure of three-color male cats, called male calico cats, appeared similar to the XXY Klinefelter's syndrome in human. Mathematical modeling and investigation of the factors that influence the infrequency of male calico cats are our main objectives of this paper. In addition, we also discuss the possible contributions and strategies to overcome the scarcity of these cats. We construct a mathematical model based on a combination of genes in the chromosome that regulates the color of cat coat on the fertilization process. The mathematical model is given as a six-dimensional system of differential equations. Sensitivity analysis is used to investigate the important parameters in the existence of male calico cats. Our finding states that the probability of normal male cats meiosis is a crucial parameter in the maintenance of the existence of male calico cats. Furthermore, one of the strategies that we could recommend in maintaining the existence of male calico cats is minimizing the value of the successful meiosis probability of normal male cats.